FOREIGN EXPERIENCE IN THE ATTRACTION AND USE OF INVESTMENTS IN EXPLORATION AND PRODUCTION OF OIL AND GAS RESOURCES - Tolkunov, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A critical analysis of foreign experience in the attraction and use of investments in oil and gas resources had been made by the author of the research. This analisis showed that the the contractual forms of subsoil use and especially Production Sharing Agreements are the effective mechanism to provide the development of mineral resources of hydrocarbons and rational subsoil use.